Finance and Development, June 1987. (Finance and Development; Finance and Development ;, 1987)
This paper reviews the World Bank lending for structural adjustment. The World Bank has always stressed the need to use limited investable resources efficiently. It has attempted to identify investment priorities in recipient countries and lent for projects that promised a high rate of return. The Bank's Operational Manual defines structural adjustment lending as nonproject lending to support programs of policy and institutional change necessary to modify the structure of an economy so that it can maintain both its growth rate and the viability of its balance of payments in the medium term.